2016
DOI: 10.1136/heartjnl-2016-309414
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation increases physical capacity but not mental health after heart valve surgery: a randomised clinical trial

Abstract: NCT01558765, Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 25 publications
3
85
0
3
Order By: Relevance
“…Only two randomized controlled trials (RCT) were performed with patients aged 60 years or older [ 91 , 92 ]. Low sample size pilot study on exercise training after TAVI, with combined endurance and resistance training, showed significant improvements in exercise capacity, muscular strength in different muscles groups, and quality of life compared with usual care [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only two randomized controlled trials (RCT) were performed with patients aged 60 years or older [ 91 , 92 ]. Low sample size pilot study on exercise training after TAVI, with combined endurance and resistance training, showed significant improvements in exercise capacity, muscular strength in different muscles groups, and quality of life compared with usual care [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is still controversy of whether CR improved mental health status. Sibilitz et al (2016) showed that CR after heart valve surgery had no effect on mental health and other measures of self-reported outcomes at 4 months. Nevertheless, the intervention consisted of monthly psycho-educational consultations.…”
Section: Discussionmentioning
confidence: 95%
“…The full week schedule is provided in appendix (Figure A1 in Appendix ). At REHPA, participants were introduced to an exercise diary shown to be effective in other patient groups independent of exercise setting (Risom et al., ; Sibilitz et al., ; Tang et al., ). Participants were encouraged to exercise three times a week during the 3 months up until follow‐up accordingly to the dairy.…”
Section: Methodsmentioning
confidence: 99%